Auditor Litigation and the Penalties on U.S. Client Firms after the Private Securities Litigation Reform Act - Nana Y. Amoah; Anthony Anderson; Isaac Bonaparte; Kyle Meyer (Journal of Accounting, Business and Management (JABM), 2018)
This study examines the relation between auditor litigation and the market and legal penalties imposed on sued audit clients after the private securities litigation reform act (PSLRA). A sample of accounting-related lawsuits is used in the regressions of three-day cumulative abnormal returns, settlement amount, and probability of settlement on auditor litigation and other variables. The results indicate a negative relation between auditor litigation and the 3-day cumulative abnormal returns around the announcement of litigation against the client firm. Another result from the study is a positive relation between auditor litigation and the legal penalty on the client firm. Specifically, the results indicate higher likelihood of settlement and larger settlement sizes for securities lawsuits in which the auditor is also sued. Our study contributes to the debate on the merit of litigation against auditors after the PSLRA. The findings imply that lawsuits against auditors appear to be a signal of audit failure and higher financial reporting risk. As audit failures erode investor confidence in the capital markets, the present study provides valuable evidence on the market and legal system’s perception of the merit of auditor litigation. The findings should be of interest to regulators and market participants given the increase in securities lawsuits against audit firms and the substantial reputational consequences of such lawsuits on audit firms and client firms.